EFFECTIVENESS OF OMALIZUMAB IN THE TREATMENT OF CHRONIC RHINOSINUSITIS WITH NASAL POLYPS: SYSTEMATIC REVIEW - Santos, Tiago Soares; Certal, VÃtor F; Gonçalves, Paulo; Carvalho, Carlos (European Scientific Journal, ESJ, 2014)
BACKGROUND: Omalizumab is a monoclonal anti-IgE antibody which reduces serum and tissue IgE levels blocking the inflammatory cascade. To date this drug has authorization for treatment of moderate-to-severe allergic asthma. The chronic rhinosinusitis with Nasal Polyps (CRSwNP) is a chronic inflammatory disease whose exact pathogenesis remains unknown. In most Caucasian patients CRS is associated with eosinophilic inflammation and local production of IgE. The aim of this systematic review was to evaluate the existing evidence on the use of omalizumab in CRSwNP. MATERIALS AND METHODS: Searches were carried out in Medline, Scopus and Cochrane Library, followed by a detailed handsearch. The search was conducted from January 1990 to December 2013. Prospective and retrospective studies were included. RESULTS: Four studies met the inclusion criteria for this systematic review: two randomized controlled trials, a retrospective case-control study and a case series. Omalizumab appears to improve both endoscopic evaluation and sinonasal inflammation, with an acceptable safety profile. However, the evidence level is low. CONCLUSIONS: The evidence shows that the use of omalizumab may be an effective therapeutic alternative in CRSwNP, especially in patients with more aggressive forms of the disease, with surgical procedures history, and bronchial asthma. However, more randomized, placebo-controlled, double-blind studies with higher number of patients are still needed to determine the efficacy of anti-IgE treatment in CRSwNP.